Effects of Light Spectrum Variation on Biomass Development of Caulerpa lentillifera: Pengaruh Variasi Spektrum Cahaya terhadap Perkembangan Biomassa Caulerpa lentillifera - Prananda, Muhammad; Muhklis, Alis; Alim, Sahrul (Yayasan Siti Widhatul Faeha, 2025)
Light spectrum plays a crucial role in photosynthesis and biomass development of marine macroalgae. This study aimed to evaluate the effects of different light spectra on biomass development of Caulerpa lentillifera in controlled cultivation systems. Four LED light treatments (white, red, yellow, and green spectra at 3000 lux intensity) were applied using a completely randomized design with three replications over 30 days. Growth parameters including absolute growth, relative growth, specific growth rate (SGR), and biomass residue were measured at 10-day intervals. Results showed that red light produced the highest absolute growth (0.107±0.004 mg), relative growth (2.39±0.15%), and SGR (0.237±0.015% day⁻¹), followed by white light (0.101±0.015 mg, 2.26±0.34%, 0.224±0.034% day⁻¹). All treatments exhibited biphasic growth patterns with peak biomass on day 10, followed by progressive decline. White light maintained the highest biomass residue (64.4±23.3%), while green light showed the lowest performance across all parameters (39.3±3.7%). The superior growth under red light is attributed to optimal absorption by photosystem II at 680 nm wavelength. This study recommends red light for maximizing short-term biomass production and white light for maintaining long-term stability in C. lentillifera cultivation systems.